Computational techniques for modeling atmospheric processes - Prusov, V. A.; Doroshenko, Anatoliy (Advances in environmental engineering and green technologies (AEEGT) book series, 2018)
This book presents recent advances in the theoretical study of the collection of basic physical and thermodynamic processes in the troposphere, the stratosphere, and the mesosphere. In these three interrelated spheres of atmospheric processes, there are valid hydrodynamic equations for modeling the various units of the general circulation of the atmosphere and weather forecasting.